Changes in life-history traits, antioxidant defense, energy metabolism and molecular outcomes in the cladoceran Daphnia pulex after exposure to polystyrene microplastics. (December 2022) - Chenxi Zhu,; Zhang, Tongqing; Liu, Xiaowei; Gu, Xiankun; Li, Daming; Yin, Jiawen; Jiang, Qichen; Zhang, Wenyi
Abstract: Ubiquitous plastic pollution is a threat to the organisms' survival and ecosystem functions, especially in aquatic environments. Although there is increasing concern about the toxicity of microplastics, knowledge about the effects of microplastics of diverse sizes and adverse impacts on freshwater organisms is still limited. In the present study, the alteration in life-history traits, antioxidant defense and energy metabolism of the model freshwater zooplankton Daphnia pulex were assessed after chronic exposure to gradient concentrations (0.5, 1, 2 and 4 mg/L) of 500-nm polystyrene microplastics (PS-MPs). Changes in protein abundance were analyzed using proteomics after exposure to 1 mg/L of PS-MPs for 14 days. The results showed that ingested PS-MPs accumulated in the digestive tract of D. pulex . 2 and 4 mg/L of PS-MPs inhibited the survival function and 4 mg/L of PS-MPs reduced the body length of D. pulex after 14 or 21 days of exposure. The exposure did not decrease the fecundity of D. pulex . After 14 days of exposure, PS-MPs changed the antioxidant capacity in a dose-dependent way and all concentrations of PS-MPs induced lipid oxidative damage. Exposure to 500-nm PS-MPs for 14 days decreased glucose and fructose contents and disturbed the lipid transport and utilization in D. pulex . Meanwhile, PS-MPs activated DNA repair and transcription regulation but inhibited lipid metabolism and response to unfolded or misfolded proteins. These results indicated that chronic exposure to 500-nm PS-MPs negatively affected D. pulex and showed similar toxic mechanisms to smaller nano-sized microplastics. Exposure to 500-nm PS-MPs resulted in restricted resources such as inhibited antioxidant capacity or energy metabolisms and D. pulex showed a potential trade-off among life-history traits to maintain fecundity at the cost of self-maintenance. The present study offers perspectives for understanding the differences in ecological effects caused by microplastics of different sizes. Graphical abstract: Image 1 Highlights: 500-nm polystyrene microplastics negatively affected D. pulex on multiple levels. 500-nm PS-MPs affected survival and body length but not fecundity of D. pulex. Impacts on antioxidant defense and metabolic disorders were observed in D. pulex. Chronic exposure to 500-nm PS-MPs changed abundance of key proteins in D. pulex. There was a potential trade-off among life-history traits in D. pulex during exposure.